A Breath of Poetry in the Classroom (2021)
The article shows the results of an investigation focused on invigorating, describing and analyzing aesthetic-interpretive experiences from the theoretical perspective hole, or respite crack, resignified by Antonio Domínguez Rey, and from positions of other scholars of poetry. It was used the educational Ethnographic approach through a qualitative nature; the research population were 32 sixth grade students from a Colombian educational establishment and the information was collected through a survey, literary liturgy and literary talk. The results showed that most of the children have contact with poetic texts; the liturgies become moments of aesthetic enjoyment, the children met living poets, listened to their voices, talked with them, read aloud some of their creations and immersed themselves in the world of poetry; With the talk they faced diverse poetic texts and by immersing themselves in them they filled with meaning the holes, cracks, or luminous voids, thus, they experienced states of reverie, through imagination and longing, amazement and emotion.